Transcriptomic profiling of neural cultures from the KYOU iPSC line via alternative differentiation protocols - Galiakberova, Adelya; Ivanov, Sergey; Golov, Arkadiy; Artyuhov, Alexander; Zolkin, Alexey; Kondratyev, Nikolay; Lagunin, Alexey; Golimbet, Vera; Dashinimaev, Erdem (Frontiers in Molecular Neuroscience, 2025)
The differentiation of pluripotent stem cells into neurons is an essential area of biomedical research, with significant implications for understanding neural development and treating neurological diseases. This study compares neural cultures derived from a common induced pluripotent stem cell line (KYOU-DXR0109B) generated by two widely adopted methods: DUAL SMAD inhibition and exogenous NGN2 overexpression. The DUAL SMAD inhibition method, which differentiates through the neural stem cell stage, produces heterogeneous cultures containing a mix of neurons, neural precursors, and glial cells. Conversely, NGN2 overexpression generates more homogeneous cultures composed predominantly of mature neurons. Transcriptomic analysis revealed significant differences in neural gene markers expression profiles, with cultures from the DUAL SMAD inhibition method enriched in neural stem cell and glial markers, while NGN2 overexpression cultures showed elevated markers for cholinergic and peripheral sensory neurons. This study underscores the importance of choosing appropriate differentiation protocols based on the desired cell types, as each method yields neural cultures with distinct cellular compositions. Understanding these differences can help optimize protocols for specific research and therapeutic applications.